2004
DOI: 10.1063/1.1829751
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of polymer-induced drag reduction in turbulent boundary layer flow

Abstract: We describe a method for direct numerical simulation of polymer-induced friction drag reduction in turbulent boundary layers. The effect of the polymer additives that induce spatial variations of skin-friction drag is included in the momentum equation through a continuum constitutive model for the viscoelastic stress, which is based on the evolution of a parameter describing the fluid microstructure. We demonstrate that the turbulence structure and polymer microstructure evolve asynchronously as one moves in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 12 publications
10
69
0
1
Order By: Relevance
“…While Considering the dependence of the complex on time and the effects of CNT on the polymer used, it was realized that DR does not relate exclusively to molecular degradation, in that, time taken for the polymer alone and that of the complex mixture before breaking down was different, upon deformation, their rearrangement as well exhibit similar trend, although (Dimitropoulos et al 2005) suggested that, it takes a period of time for turbulent structures rearrangement after such deformation, as such DR ultimate level is not achieved by DR immediately, therefore making DR a complicated function with respect to time.…”
Section: Comparing the Complex With Nanofluidsmentioning
confidence: 99%
“…While Considering the dependence of the complex on time and the effects of CNT on the polymer used, it was realized that DR does not relate exclusively to molecular degradation, in that, time taken for the polymer alone and that of the complex mixture before breaking down was different, upon deformation, their rearrangement as well exhibit similar trend, although (Dimitropoulos et al 2005) suggested that, it takes a period of time for turbulent structures rearrangement after such deformation, as such DR ultimate level is not achieved by DR immediately, therefore making DR a complicated function with respect to time.…”
Section: Comparing the Complex With Nanofluidsmentioning
confidence: 99%
“…The measured profile affected by the wall roughness slightly moves down relative to the profile of the case with smooth wall. For the case with polymer injection, although the upward shift of the mean velocity profile in the logarithmic region is very evident, the slope of the logarithmic region is lower than that of the flow with homogeneous polymer solution [22,37,38]. When the polymer drag-reduced flow with low DR transforms to the flow with high DR, the logarithmic region representing the inertial effects vanishes gradually.…”
Section: Mean Streamwise Velocitymentioning
confidence: 98%
“…In more recent work, a large number of numerical simulations based on the constitutive equations of polymer solution including the most often used finitely extensible nonlinear elastic with Peterlin approximation (FENE-P) constitutive equation [18] have also been developed for investigating Toms effect with homogeneous polymer solutions [19][20][21][22][23][24][25]. Den Toonder et al [26] posited that viscous anisotropic stress was the main reason for drag reduction by using two different constitutive equations.…”
Section: Advances In Mechanical Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…This method used recycling of the downstream data to provide the inlet boundary condition on the inflow simulation (illustrated in Figure 1). It has been successfully applied in both incompressible and compressible boundary layer simulations [3][4][5]. Despite the wealth of publications that have successfully applied this method, a number of studies [5][6][7][8][9][10] have indicated that some aspects of LWS method can prove difficult to implement.…”
Section: Introductionmentioning
confidence: 99%